The interplay of saliva, erosion and attrition on enamel and dentine - I. Aljulayfi; S. O'Toole; M. Healy; S. Sumaidaa; Z. Ali; D. Bartlett; R. Austin (Saudi Dental Journal)
Purpose: This investigation aimed to compare the protective role of saliva against erosion and attrition challenges. Method: Polished enamel and dentine samples (n = 160) were prepared and randomly assigned to either the saliva or saliva-free group (n = 40 enamel and n = 40 dentine/group). Within each subgroup, they were allocated to four subgroups: negative control (deionized water exposure 10 min), erosion (0.3% citric acid 10 min), attrition (120 S of 300 g force), or combined erosion/attrition (0.3% citric acid 10 min then 120 S of 300 g force). Experimental cycles were repeated three times. Data analysis was performed using SPSS. Results: The mean and standard deviation (SD) of step heights produced by the attrition and erosion/attrition groups in enamel in the saliva-free group were 5.6 µm (2.4) and 13.4 µm (2.8), respectively, while they were 2.4 µm (3.8) and 12.9 µm (3.5) in the saliva group, with no significant difference between the saliva and saliva-free groups. For dentine, the corresponding step heights were 25.2 µm (5.5) and 35.9 µm (7.9) for the saliva-free group, but 21.8 µm (5.3) and 27.3 µm (6.4) for the saliva group (p < 0.001). Conclusion: There was a trend that saliva decreased wear, but this was only statistically significant for erosion/attrition dentine wear.